Knowledge, Learning, and IT: A Competence-Based Approach to Employee Performance - Fredy Kundarto; Azhar Affandi; Denok Sunarsi (Program Doktor Ilmu Manajemen, Universitas Pasundan, Indonesia, 2025)
This study is motivated by the challenges faced by PT Regulus Inspira Land in improving employee performance amid globalization, advances in information technology, and the need for adequate competencies. Issues include the suboptimal implementation of knowledge management, an underdeveloped learning organization culture, limited digital skills, and employee competency gaps. The research aims to analyze the effect of knowledge management, learning organization, and information technology development on employee performance, with competence as an intervening variable. A descriptive-associative quantitative approach was applied using a questionnaire survey of PT Regulus Inspira Land employees in Depok, West Java, during 2025. The results indicate that all three independent variables positively influence competence, which in turn directly and indirectly enhances employee performance. The findings highlight that strengthening competence is key to maximizing the benefits of knowledge management, organizational learning, and technology adoption. Recommendations include developing technology-based training programs, reinforcing a continuous learning culture, and optimizing integrated knowledge management systems to sustainably improve employee performance.